HUBUNGAN PENYAKIT GINJAL KRONIS PREDIALISIS DENGAN BEBERAPA PARAMETER PENYAKIT ATEROSKLEROSIS ARTERI KAROTIS - Sutarka, Nyoma; Suwitra, Ketut; Loekman, Jodi S; Sudhana, Wayan; Kandarini, Yenny; Martadiani, Elysanti Dwi; Margian, Nyoman (journal of internal medicine, 2010)
Carotid artery intima media thickness (cIMT) is valid marker of subclinical atherosclerosis because it gives sign of earlyatherosclerosis process. We conduct this study to know the relationship between predialysis chronic kidney disease (CKD) withseveral parameters of carotid arterial atherosclerosis.A cross sectional study was done in patients with predialysis CKD who came to outpatient Clinic of Nephrology inSanglah General Hospital from May 2009. CKD criteria is based on KDQQI 2003. Estimated Glomerular Filtration Rate (eGFR)was calculated with Cockroft-Gault formula. Measurement of cIMT is done by USG B-Mode with USG Logig-5.There were 30 patients (20 with eGFR < 60 ml/mnt and 10 with eGFR 60 ml/mnt). Mean of cIMT in eGFR < 60ml/mnt: right/left cIMT1 0.24445 ± 0.3096/0.3210 ± 0.4006 mm; IMT2 0.2405 ± 0.3138/0.2825 ± 0.3971 mm; IMT3 0.2315 ±0.3026/0.2820 ± 0.3672 mm; bifurkatio IMT 0.3115 ± 0.4069/0.3515 ± 0.4991 mm; total IMT 0.6350 ± 0.1738/0.6938 ± 0.1912mm. For eGFR > 60 ml/mnt: right/left IMT1 0.1120 ± 0.1722/0.1030 ± 0.1398 mm; IMT2 0.0880 ± 0.1103/0.1130 ± 0.1718mm; IMT3 0.1010 ± 0.1408/0.1170 ± 0.1700 mm; bifurcatio IMT 0.1920 ± 0.3545/0.1980 ± 0.3527 mm, total IMT 0.6250 ±0.1269/0.6750 ± 0.1124 mm. There was signiÞ cant difference in eGFR < 60 ml/mnt the left IMT1 (MD: 0.21 CI95% 0.01 ! 0.42;p = 0.038). Five out of 20 patients with eGFR < 60 ml/mnt and 6 among 10 patients of eGFR 60 ml/mnt were found plaques.There are no signiÞ cant difference of plaque location, plaque width, and lumen diameter between carotid arterial with andwithout plaque. As a conclusion we found there is no signiÞ cant difference between predialysis CKD with several parameters ofcarotid arterial atherosclerosis but cIMT tends to be thicker on predialysis CKD patients with eGFR < 60 ml/mnt.